THE ANALYSIS OF THE AWARENESS STAGE OF STUDENTS THAT STUDY IN THE FACULTY OF SPORT SCIENCES TOWARDS THE EFFECT OF SPORT ON INDIVIDUALS WITH MENTAL DISABILITY SAMPLE of FIRAT UNIVERSITY - Kırtepe, Abdurrahman (METİN YAMAN, 2017)
The aim of this research is to determine the opinions of students that study in the faculty of sport sciences on the developments of sport in social, physical, mental and psychological dimensions upon individuals with mental disability according to some variables, and to figure out and to evaluate their awareness levels on this topic 92 female and 132 male students at total 224 students that still actively study in the faculty of sport sciences of Fırat University in 2015- 2016 academic year spring term participated in this research voluntarily. In research as a data collection tool, beside 5 question personal info form prepared by researcher to determine the personal info distribution of participants, 32 question “Awareness Scale for The Effect of Sport on Individuals with Mental Disability” developed by Ilhan E,L and Esenturk O 2015 were used. Scale was comprised of 32 articles and one dimension. For the entire scale, Croanbach Alpha reliability coefficient is 0.989. As a result; it was determined that awareness levels of female students compared to male students that study in the faculty of sport sciences in Fırat University towards the developments of sport in social, physical, mental and psychological dimensions upon individuals with mental disability are higher p